Frailty and risk of gastrointestinal bleeding: a prospective cohort study based on UK biobank - Chenao Zhang; Chenao Zhang; Qiming Huang; Xingyu Liu; Jiren Wang; Junyan Wang; Jian Song; Rong Song; Hong Su; Qiao Mei (Frontiers in Public Health)
IntroductionFrailty has been associated with various diseases. However, its impact on gastrointestinal bleeding (GIB) remains largely unexplored. This study investigates the relationship between frailty and the incidence of gastrointestinal bleeding events.MethodsA total of 352,060 participants from the UK Biobank with no history of gastrointestinal bleeding were included. Baseline frailty status was assessed using the Fried phenotype and categorized as non-frail, pre-frail, or frail. The primary outcome was gastrointestinal bleeding, identified through hospitalization records and death registries. Cox proportional hazard models were used to evaluate the association between frailty and gastrointestinal bleeding incidence.ResultsAmong the 352,060 participants (mean age 56.1 years), 3.6% (N = 12,747) were classified as frail, and 43.6% (N = 153,424) as pre-frail at baseline. Over a median follow-up of 14.7 years, 20,105 gastrointestinal bleeding events were recorded. Compared to non-frail individuals, frail (HR = 1.53, 95% CI: 1.44–1.62) and pre-frail (HR = 1.15, 95% CI: 1.11–1.18) individuals exhibited a significantly higher risk of gastrointestinal bleeding after multivariate adjustment (P for trend < 0.001). Subgroup and sensitivity analyses remained consistent findings.ConclusionFrailty significantly elevates the risk of gastrointestinal bleeding. Early identification and targeted multidimensional interventions addressing frailty may reduce gastrointestinal bleeding events and improve patient prognosis.